Metabolomic approach of the antiprotozoal activity of medicinal Piper species used in Peruvian Amazon - Vásquez-Ocmín, Pedro G. (2021)
Ethnopharmacological relevance: In the Peruvian Amazon as in the tropical countries of South America, the use of medicinal Piper species (cordoncillos) is common practice, particularly against symptoms of infection by protozoal parasites. However, there is few documented information about the practical aspects of their use and few scientific validation. The starting point of this work was a set of interviews of people living in six rural communities from the Peruvian Amazon (Alto Amazonas Province) about their uses of plants from Piper genus: one community of Amerindian native people (Shawi community) and five communities of mestizos. Infections caused by parasitic protozoa take a huge toll on public health in the Amazonian communities, who partly fight it using traditional remedies. Validation of these traditional practices contributes to public health care efficiency and may help to identify new antiprotozoal compounds. Aims of study: To record and validate the use of medicinal Piper species by rural people of Alto Amazonas Province (Peru) and annotate active compounds using a correlation study and a data mining approach. Materials and methods: Rural communities were interviewed about traditional medication against parasite infections with medicinal Piper species. Ethnopharmacological surveys were undertaken in five mestizo villages, namely: Nueva Arica, Shucushuyacu, Parinari, Lagunas and Esperanza, and one Shawi community (Balsapuerto village). All communities belong to the Alto Amazonas Province (Loreto region, Peru). Seventeen Piper species were collected according to their traditional use for the treatment of parasitic diseases, 35 extracts (leaves or leaves and stems) were tested in vitro on P. falciparum (3D7 chloroquine-sensitive strain and W2 chloroquine-resistant strain), Leishmania donovani LV9 strain and Trypanosoma brucei gambiense. Assessments were performed on HUVEC cells and RAW 264.7 macrophages. The annotation of active compounds was realized by metabolomic analysis and molecular networking approach. Results: Nine extracts were active (IC50 ≤ 10 μg/mL) on 3D7 P. falciparum and only one on W2 P. falciparum, six on L. donovani (axenic and intramacrophagic amastigotes) and seven on Trypanosoma brucei gambiense. Only one extract was active on all three parasites (P. lineatum). After metabolomic analyses and annotation of compounds active on Leishmania, P. strigosum and P. pseudoarboreum were considered as potential sources of leishmanicidal compounds. Conclusions: This ethnopharmacological study and the associated in vitro bioassays corroborated the relevance of use of Piper species in the Amazonian traditional medicine, especially in Peru. A series of Piper species with few previously available phytochemical data have good antiprotozoal activity and could be a starting point for subsequent promising work. Metabolomic approach appears to be a smart, quick but still limited methodology to identify compounds with high probability of biological activity. © 2020 Elsevier B.V.